Análisis de los formatos más utilizados para compartir noticias falsas en facebook - Astudillo Mancilla, Flora Paulina (2020)
This research focused on analyzing the most used formats to share fake news on Facebook; For this, a “Case Study” was carried out because it allows an in-depth investigation of the different ways that users use to share false news. Since currently misinformation has taken a lot of force in social networks (Facebook), false news circulates constantly, more frequently than expected, which makes users share this news without any type of verification. With the implementation of the search for the concepts of format, sharing, news, fake news, and Facebook for the correct understanding of the research, preceding the explanation of the most used formats, which are four: Emotional narrative constructions and memes, Altered, fabricated, or decontextualized images and videos, disinformation infiltrators and orchestrated campaigns, fake websites, and fake authorized personalities. Finally, it was concluded that, despite the great fight against disinformation by Facebook, these formats are still being used by several users.